Congenital pericardial defect with Gerbode type septal defect in rotated heart: report of a case - Haponiuk, Ireneusz; Chojnicki, Maciej; Jaworski, Radosław; Sroka, Mariusz; Steffek, Mariusz; Czauderna, Piotr (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Asymptomatic pericardial defects are rare and found mostly incidentally during cardiac surgery. In one third of all cases absence of pericardium accompanies various congenital heart defects, and is diagnosed intraoperatively. We present a case of an 8-month-old male infant with Gerbode-type septal defect (LV-RA communication) with rightward rotation of the heart and left-sided partial pericardial defect, with pericardial adhesions and symptoms of left-sided pressure pneumothorax while opening the pericardial sac. The unique co-existence of Gerbode septal communication and position anomaly of the heart with congenital defect of the pericardium caused the effect of valvular air-trapping mechanism in the area of pericardial wall discontinuity that needed a change of the operative strategy prior to cardiopulmonary bypass. Taking into account the patient’s past medical history the pericardial defect could be responsible for pericardial adhesions as a reaction to recurrent pulmonary infections spreading via persistent pleuro- pericardial communication.